miR-133a Regulates Vitamin K 2,3-Epoxide Reductase Complex Subunit 1 (VKORC1), a Key Protein in the Vitamin K Cycle - Pérez-Andreu, Virginia (ScholarOne, 2012)
Regulation of key proteins by microRNAs (miRNAs) is an emergent field in biomedicine. Vitamin K 2,3-epoxide reductase complex subunit 1 (VKORC1) is a relevant molecule for cardiovascular diseases, since it is the target of oral anticoagulant drugs and plays a role in soft tissue calcification. The objective of this study was to determine the influence of miRNAs on the expression of VKORC1. Potential miRNAs targeting VKORC1 mRNA were searched by using online algorithms. Validation studies were carried out in HepG2 cells by using miRNA precursors; direct miRNA interaction was investigated with reporter assays. In silico studies identified two putative conserved binding sites for miR-133a and miR-137 on VKORC1 mRNA. Ex vivo studies showed that only miR-133a was expressed in liver; transfection of miRNA precursors of miR-133a in HepG2 cells reduced VKORC1 mRNA expression in a dose-dependent manner, as assessed by quantitative reverse transcriptase–polymerase chain reaction (qRT-PCR) as well as protein expression. Reporter assays in HEK293T cells showed that miR-133a interacts with the 3′UTR of VKORC1. Additionally, miR-133a levels correlated inversely with VKORC1 mRNA levels in 23 liver samples from healthy subjects. In conclusion, miR-133a appears to have a direct regulatory effect on expression of VKORC1 in humans; this regulation may have potential importance for anticoagulant therapy or aortic calcification.